Cystine accumulation attenuates insulin release from the pancreatic β‐cell due to elevated oxidative stress and decreased ATP levels. (18th November 2015) - McEvoy, Bernadette; Sumayao, Rodolfo; Slattery, Craig; McMorrow, Tara; Newsholme, Philip
Abstract : Key points: In cystinosis, a lysosomal storage disorder, an altered redox state has been suggested as contributing to cellular dysfunction. Ctns gene knockdown in a pancreatic β‐cell line caused increased cystine levels. Attenuated nutrient stimulated insulin secretion was observed after Ctns knockdown which may have been caused by an increase in oxidative stress. Oxidative stress may reduce ATP production in pancreatic β‐cells resulting in attenuated insulin release. The redox‐sensitive transcription factor NF‐κB was activated after Ctns knockdown which may contribute to the increased incidence of apoptosis. Abstract: The pancreatic β‐cell has reduced antioxidant defences making it more susceptible to oxidative stress. In cystinosis, a lysosomal storage disorder, an altered redox state may contribute to cellular dysfunction. This rare disease is caused by an abnormal lysosomal cystine transporter, cystinosin, which causes excessive accumulation of cystine in the lysosome. Cystinosis associated kidney damage and dysfunction leads to the Fanconi syndrome and ultimately end‐stage renal disease. Following kidney transplant, cystine accumulation in other organs including the pancreas leads to multi‐organ dysfunction. In this study, a Ctns gene knockdown model of cystinosis was developed in the BRIN‐BD11 rat clonal pancreatic β‐cell line using Ctns ‐targeting siRNA. Additionally there was reduced cystinosin expression, while cell cystine levels were similarly elevated to the cystinotic state. Decreased levels of chronic (24 h) and acute (20 min) nutrient‐stimulated insulin secretion were observed. This decrease may be due to depressed ATP generation particularly from glycolysis. Increased ATP production and the ATP/ADP ratio are essential for insulin secretion. Oxidised glutathione levels were augmented, resulting in a lower [glutathione/oxidised glutathione] redox potential. Additionally, the mitochondrial membrane potential was reduced, apoptosis levels were elevated, as were markers of oxidative stress, including reactive oxygen species, superoxide and hydrogen peroxide. Furthermore, the basal and activated phosphorylated forms of the redox‐sensitive transcription factor NF‐κB were increased in cells with silenced Ctns . From this study, the cystinotic‐like pancreatic β‐cell model demonstrated that the altered oxidative status of the cell, resulted in depressed mitochondrial function and pathways of ATP production, causing reduced nutrient‐stimulated insulin secretion. Abstract :